2013
DOI: 10.4103/0970-9290.123363
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for future caries control: A short-term clinical study

Abstract: The use of probiotic products could be an alternative strategy of displacing pathogenic microorganisms by probiotic bacteria and can thus be exploited for the prevention of enamel demineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Significant reduction in salivary mutans streptococci ( P ≤ 0.05) was found in our study after consumption of probiotic curd, which was in accordance to the previous studies done by Chinnappa et al .,[2] Caglar et al .,[6] Caglar E, et al .,[8] and Zhu et al . [9] in which a statistically significant reduction of salivary mutans streptococci was recorded after probiotic yogurt consumption ( P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Significant reduction in salivary mutans streptococci ( P ≤ 0.05) was found in our study after consumption of probiotic curd, which was in accordance to the previous studies done by Chinnappa et al .,[2] Caglar et al .,[6] Caglar E, et al .,[8] and Zhu et al . [9] in which a statistically significant reduction of salivary mutans streptococci was recorded after probiotic yogurt consumption ( P ≤ 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…This was in accordance with the study done by Chinnappa et al . [2] in which after 1 h and 7 days, statistically significant ( P ≤ 0.05) results were obtained.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the majority of studies examining the effect of probiotics on the oral microflora, probiotics were consumed for up to 15 days, which is in line with the methodology adopted in the present investigation [6,[18][19][20][21][22][23][24][25]. The most commonly studied probiotics are those contained in fortified milk, ice cream, yogurt, and other dairy products.…”
Section: Discussionmentioning
confidence: 92%
“…The most commonly studied probiotics are those contained in fortified milk, ice cream, yogurt, and other dairy products. For example, Chinnappa et al [24] observed a decrease in S. mutans count after a week-long daily consumption of ice cream and whey containing a probiotic. Similar results were obtained by Caglar et al [6] with Bifidobacterium lactis, Jiang et al [17] with the probiotic L. rhamnosus, Hedayati-Hajikand [11] with ProBiora3® blend of three strains of probiotic bacteria (S. uberis KJ2™, S. oralis KJ3™, S. rattus JH145™), and Burton et al [26] using S. salivarius M18.…”
Section: Discussionmentioning
confidence: 99%